Combining high-flow nasal cannula oxygen therapy with repeated toilet bronchoscopies for respiratory failure due to excessive infected airway secretions: a case report and series from a non-intensive hospital ward - Fimognari, Filippo Luca; Baffa Bellucci, Francesco; Fedele, Flavio; Scarlata, Simone; Armentaro, Giuseppe; Sciacqua, Angela (Frontiers in Medicine, 2024)
Fiberoptic bronchoscopy (FBO) has diagnostic or therapeutic purposes but can cause respiratory deterioration, particularly in patients with pre-existing acute respiratory failure (ARF). Non-invasive ventilation (NIV) and high-flow nasal cannula oxygen therapy (HFNC) are used as respiratory support for ARF as well as to prevent significant oxygen deterioration during FBO. The combined use of NIV and early therapeutic FBO to clear retained abundant infected secretions from the airways may be an alternative to intubation and invasive mechanical ventilation (IMV), but no data exist on the combined use of FBO and HFNC. A 78-year-old male patient with ARF secondary to chronic obstructive pulmonary disease (COPD) exacerbation and pneumonia was admitted to our non-intensive geriatric ward. After an initial improvement, his respiratory conditions worsened. While continuing HFNC, he underwent a series of eight FBOs over 9 days, each performed in response to significant decreases in peripheral oxygen saturation (SpO2). The goal was to remove copious and occlusive infected secretions from the airways, with each procedure resulting in good SpO2 recovery. After etiological targeted antibiotic therapy based on bronchial aspirate, the patient improved and was discharged. Next, six consecutive similar ARF patients were treated using the same strategy of combining HFNC with repeated toilet FBO performed within the ward to clear secretions. All patients showed improvement and were discharged. The combination of HFNC and repeated toilet FBO could be a safe and effective intervention in non-intensive wards to prevent intubation and IMV in frail and elderly patients with ARF secondary to copious and occlusive infected secretions in the airways.